The nuclei of the lateral lemniscus: unexpected players in the descending auditory pathway - Gómez-Martínez, Mario; Rincón, Héctor; Gómez-Álvarez, Marcelo; Gómez-Nieto, Ricardo; Saldaña, Enrique (Frontiers in Neuroanatomy, 2023)
Introduction In the mammalian auditory pathway, the nuclei of the lateral lemniscus (NLL) are thought to be exclusively involved in the bottom-up transmission of auditory information. However, our repeated observation of numerous NLL neurons labeled after injection of retrograde tracers into the superior olivary complex (SOC) led us to systematically investigate with retrograde tracers the descending projections from the NLL to the SOC of the rat. Methods We performed large injections of FluoroGold into the SOC to determine NLL contributions to descending projections, and focal injections of biotinylated dextran amine (BDA) to pinpoint the specific nuclei of the SOC innervated by each NLL. Results The SOC is innervated by thousands of neurons distributed across four nuclei or regions associated with the lateral lemniscus: the ipsilateral ventral and intermediate nuclei of the lateral lemniscus (VNLL and INLL); the medial paralemniscal region (PL) of both sides; and the ipsilateral semilunar nucleus (SLN), a previously unrecognized nucleus that wraps around the INLL dorsally, medially, and caudally and consists of small, flat neurons. In some experiments, at least 30% of neurons in the VNLL and INLL were retrogradely labeled. All nuclei of the SOC, except the medial and lateral superior olives, are innervated by abundant lemniscal neurons, and each SOC nucleus receives a unique combination of lemniscal inputs. The primary target of the projections from the VNLL is the ventral nucleus of the trapezoid body (VNTB), followed by the superior paraolivary nucleus (SPON), and the medial nucleus of the trapezoid body (MNTB). The INLL selectively innervates the VNTB. The PL innervates dorsal periolivary regions bilaterally. The SLN preferentially innervates the MNTB and may provide the first identified non-calyceal excitatory input to MNTB neurons. Discussion Our novel findings have strong implications for understanding acoustic information processing in the initial stages of the auditory pathway. Based on the proportion of lemniscal neurons involved in all the projections described, the NLL should be considered major players in the descending auditory pathway.